Endemic fishes of Arunachal Pradesh, India with distribution and conservation status - Gurumayum, Shantabala (Journal of the Inland Fisheries Society of India, 2023)
At present, a total of 53 fish species which come under 4 orders, 12 families and 22 genera were found endemic to the state of Arunachal Pradesh. Nemacheilidae having 16 species under 3 genera has the maximum number of representative species followedby Sisoridae 13 species and Cyprinidae with 12 species each under 7 and 2 genera, respectively. Amblycipitidae and Channidae were represented by two species each under single genus whereas Bagridae was represented by two genera and two families. Six families viz., Badidae, Balitoridae, Cobitidae, Danionidae, and Psilorhynchidae, Synbranchidae were monotypic families representingsingle species. Conservation status of only 7 endemic fish species of the state were evaluated under the IUCN Red List of Threatened Species (version 2021-1) where 3 species viz., Amblyceps arunachalensis, Devario horai and Lepidocephalichthys arunachalensis werefound to be included in Endangered Category whereas Pseudecheneis sirenica was categorized under Vulnerable; Aborichthys kempi in Near Threatened; Erethistoides senkhiensis under Data Deficient and Garra kempi under Least Concerned categories.During the study, it was found that conservation status of the majority of the endemic fishes (46) of the state were not available. All the 53 endemic fish species reported during the study were discovered from the state and some of the species were not recorded further other than their type localities. Fishes having limited distribution to some specific areas are more vulnerable to extinction largely due to anthropogenic threats such as habitat destruction, over exploitation and human invasion which are happening rampantly in the state at present.